71 HEMOBILIA AFTER LAPAROSCOPIC CHOLECYSTECTOMY: CASE REPORT. (1st January 2006) - Barriga, J.; Mathews, C.; Marino, C.; Tombazzi, C.
Abstract : Introduction: Laparoscopic cholecystectomy is the ideal management of symptomatic cholelithiasis. Hemobilia is a rare complication of this procedure. We present a case of hemobilia 7 days after laparoscopic cholecystectomy. Clinical presentation, radiologic findings, outcome, and management are discussed. Case Report: 50 yo female, who underwent elective laparoscopic cholecystectomy, without complications, for symptomatic cholelithiasis. One week after surgery she was admited to the hospital with 3 days of RUQ pain, nausea, vomiting, and abnormal liver function tests (bilirubin: 2.1 mg/dL, alkaline phosphatase: 138 IU/L, AST: 645 U/L, ALT: 273 U/L). HIDA scan was normal. A CT scan described a possible hematoma at the gallbladder fossa. Three days after admission bilirubin increased to 4.9 mg/dL, and the hematocrit decreased from 42% to 34.8%. Patient underwent an endoscopic retrograde cholangiogram (ERC), which showed active bleeding from the major ampulla. Cholangiogram demonstrated multiple filling defects in common bile duct and common hepatic duct, but no ductal dilatation. Sphincterotomy was performed and a balloon was dragged through the common bile duct, obtaining few blood clots. An arteriogram was done, which showed a thrombus at the base of the right hepatic artery with possible dissection. No pseudoaneurysm. No active bleeding was found or embolization done. The patient remained clinically stable, with normalization of LFT. Discussion: Hemobilia is a rare complication, mostly caused by either blunt or penetrating trauma (up to 48% of cases); also described in cases of infection, gallstones, tumor, pancreatitis, aneurysms. Only a few cases have been reported as a complication from laparoscopic cholecystectomy. Imaging studies that may help in the diagnosis are CT scan, ultrasound, and nuclear scan. ERC confirms the diagnosis, after which arteriogram should be done since it is the most accurate test to locate the lesion and can also be therapeutic with embolization of the bleeding vessel. The patient presented in this case remained clinically stable without further surgical/medical intervention. Hemobilia should be considered in a patient who presents with abdominal pain and abnormal liver function test after laparoscopic cholecystectomy.